Spectroscopic analysis and cytotoxic activity of quas-sinoid isolated from the seeds of Brucea javanicaon Hela cell - Sonlimar Mangunsong; Dwiprahasto I; Mustofa .; Jumina . (Indonesian Journal of Pharmacy, 2011)
The  quassinoids  from  Brucea  javanica exhibit  biological  activities  as antimalarial,  antitumor,  antiviral  and  antiamoebic  activities.  These  quassinoids having  a  promising  antitumor  activity.This  research was  aimed  to  isolated quassinoid  (bruceine  A,  MW  522  g/mol)   compound  from  B.  javanica and  to investigate  the  cytotoxicity  of  bruceine  A  under  invitro conditions  in  Hela  cells. The  cytotoxicity  assays   using   MTT  assay.  The  bruceine   showed  a  good cytotoxic  activity  in  Hela cells  at  24  hours  with  doxorubicine  as  a  positive control.  Structural  elucidation  of   bruceine   is  done  by   using  UV  and  FT-IR spectra,  NMR  spectra   recorded  on  Tesla  av600,  (400 MHz) 1HNMR  in  pyridine (D5),  some  in  Gyro  (300  MHz) 1HNMR  in  acetone-(d6),  DMSO-(d6)  and  CdCl3 ,13CNMR,  75  MHz,  mass  spectra  on  biospectrometry  LC-MS.  Analytical  HPLC retention time,tRwas 4.617 minutes (Met/H20) 60:40. Its Molecular formula was determined  to  be  (  C26 H34  O11)  by  the  [M+H]+ ion  peak  at  m/z  523 and  m/z 1045 confirmed by High Resolution mass spectra Orbitrap (HRESIMS). From the results demonstrated that could be bruceine A compound refers to our spectral data.  Its  has   activity  in  IC50 value  191,5  µM  on  Hela  Cells  under  invitro conditions.Key words: Quassinoid, B. javanica,Brusein A, Spectroscopic, Anticancer